2005
DOI: 10.1586/14737159.5.4.613
|View full text |Cite
|
Sign up to set email alerts
|

Automated chip-based device for simple and fast nucleic acid amplification

Abstract: A chip-based PCR device is presented that is capable of rapid temperature ramping and handling sample volumes in the microliter range. The PCR chip comprises a microchannel thermally connected to three temperature zones. Inside this microchannel, the PCR sample plug is driven and precisely positioned by a ferrofluidic actuator for more than 40 cycles within 5 min. Computer simulations predict that the sample plugs are thermally equilibrated on a time scale of some 10 ms when transported to a different temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 10 publications
0
29
0
2
Order By: Relevance
“…One application example reported recently is the use of an air vent as a chip-integrated valve for positioning of a liquid plug. 12 We found that the air vents a) Author to whom correspondence should be addressed. Electronic mail: mhqgong@ntu.edu.sg.…”
Section: Introductionmentioning
confidence: 98%
“…One application example reported recently is the use of an air vent as a chip-integrated valve for positioning of a liquid plug. 12 We found that the air vents a) Author to whom correspondence should be addressed. Electronic mail: mhqgong@ntu.edu.sg.…”
Section: Introductionmentioning
confidence: 98%
“…The microchannel of the oscillatory-flow PCR can be constructed in such substrates as silicon (Bu et al 2003;Wang et al 2005), glass (Sugumar et al 2010), quartz (Baker et al 2003), and various polymers (for example SU-8 (Auroux et al 2003b, 2004a, poly(methylmethacrylate) (PMMA) (Hardt et al 2004;Münchow et al 2005;Cheng et al 2005), cycloolefin copolymer (COC) (Hardt et al 2004;Münchow et al 2005), polydimethylsiloxane (PDMS) (Hu et al 2006;Frey et al 2007;Ugsornrat et al 2008), polycarbonate (PC) (Ohashi et al 2007), and dry film resist (DFR) ). To form a chip with sealed channels, these chips are required to bond with another cover plate.…”
Section: Introductionmentioning
confidence: 99%
“…(2) The reactor' s heater and sensor elements. The heaters used for the oscillatoryflow PCR have changed from the metal/ceramic blocks with a certain heating cartridge (Chiou et al 2001(Chiou et al , 2002Auroux et al 2003a;Hardt et al 2004;Münchow et al 2005;Frey et al 2007;Sugumar et al 2010) to the Peltier heater (Chen et al 2007b;Paik et al 2007) and the film heaters integrated on the chips (for example indium tin oxide (ITO) (Cheng et al 2005), platinum (Bu et al 2003;Wang et al 2005;Polini et al 2010;Sciancalepore et al 2011), chromium/aurum (Ugsornrat et al 2008), and others (Baker et al 2003;Auroux et al 2003bAuroux et al , 2004aSista et al 2008)). And, the temperature sensor elements include the commercially available thermocouples (Chiou et al 2001(Chiou et al , 2002Auroux et al 2003a;Chen et al 2007b;Paik et al 2007), the thermistors (Sista et al 2008;Sugumar et al 2010), and the on-chip film sensors (Bu et al 2003;Wang et al 2005;Polini et al 2010;Sciancalepore et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations